Experimental evaluation of heat transfer and pressure drop performance of internally finned tubes. - Rizvi, S. Tanweer H. (University of Ottawa (Canada), 1978)
Heat transfer and pressure drop measurements were made on three test tubes, a quintuplex tube, and two single finned tubes. The single finned tubes tested were of the high spiral type. The spiral finned tubes have been arbitrarily classified in the literature as low spiral with fin height to inside diameter ratio r < 0.065, and as high spiral with the ratio r ≥ 0.065. Lubricating oil was used as the test fluid. Three sets of test runs were performed on each of three test sections, fixing the values of the oil inlet temperature and water flow rate in each set, while varying the oil flow rate to cover as much as possible a wide range of operating conditions. Effects of oil inlet temperature and cooling water flow rate on the performance of test tubes were also investigated. At almost the same operating conditions it was found that the quintuplex finned tube provides a sizable decrease in heat transfer area, but at the expense of high pumping power requirement. It is, therefore, suggested that quintuplex tube should be preferred in industrial applications in which the size of the heat exchanger is an important factor. But if the pumping power is the criterion for selection, the single-finned tube is superior.
Keywords: Engineering, Mechanical.